A financeirização da educação brasileira e seus impactos: do nível superior ao ensino básico - Blandy, Beatriz de Azevedo (2022)
The raison d'être of this work is to point out the impacts of the increasing privatization of educational services, relating it to the intensification of the financialization and commodification of education. This process is described based on the growth of access to higher education in recent decades, extending this research to its most recent frontier, basic education. In this way, a historical course of this phenomenon is weaved, locating it in a broader context, emphasizing the impacts of the transformations that this course proposes for the sector and for Brazilian society. In this sense, our intention is to explore the chain that relates aspects and processes of these financialization movements with the changes addressed to school organizations, their educational purposes, and objectives, which in turn impact teachers, students, their collectivities, the social fabric and, without doubt, future scenarios